Witterungsbedingte Schwankungen der Ernährungsbasis in Afghanistan - Rathjens, Carl (ERDKUNDE, 1975)
In Afghanistan the droughts of 1970 and 1971 caused crop failures, loss of livestock and in some regions even famine, but the humid years of 1972 and 1973 (first half) permitted export of cereals again after a long time. Therefore the relations between precipitation and crop yields are examined. After a short survey of the development of the meteorological service it is demonstrated that the production of cereals depends not so much on the mean annual precipitation, but on the amount of winter precipitation, the proportion of spring rains from March to May and the abundance of snow in the mountains. Rainfall agriculture (lalmi) in humid years is possible in the whole of Northern and Eastern Afghanistan, but only in the mountainous area of the outermost Northeast in dry years. Also the susceptibility to droughts and crop failures has increased consider ably for different reasons. In the arid climate the extreme years are more meaningful for investigations in agricultural geography and geoecology than average data obtained from longer observation series.